Challenges in Urban Mobility and the Way Forward : A Study of Maseru, Lusaka, and Harare Cities - World Bank (World Bank, Washington, DC, 2020)
This report is the outcome of brief visits to three cities - Maseru, Lusaka, and Harare, culminating in a Southern Africa regional workshop in Livingstone in May 2019. The objective of this workshop was to: (a) develop an understanding of the complexity of urban transport; (b) learn from international experience; and (c) develop a common platform where the smaller capital cities in Southern Africa can exchange ideas and consider options to address their current urban mobility issues. Three simultaneous trends present significant transport challenges to cities in developing countries. The first two make the third even more dramatic and impactful. They are: rapid urbanization; rapid economic development and income growth; and rapid motorization. The report is divided into eight sections. The first three sections focus on the overall challenges faced by the cities and their institutional, strategic planning, and policy contexts. Sections 4 and 5 describe the road infrastructure characteristics and challenges faced by public transport and nonmedical transportation (NMT), which form the main focus of this report. Chapter 6 outlines the distinct issues faced by women and the physically challenged. The last two sections outline the focus of attention needed to address the growing challenges of urban mobility and the way ahead.